Oestrogen-related tumour phenotype: positron emission tomography characterisation with (18)F-FDG and (18)F-FES - Tsujikawa, T (The British Institute of Radiology., 2012)
This article outlines the role of 16α-[(18)F]fluoro-17β-oestradiol ((18)F-FES) positron emission tomography (PET) combined with 2-[(18)F]fluoro-2-deoxy-D-glucose ((18)F-FDG) in patients with oestrogen-related tumours for evaluating tumour phenotype. (18)F-FES-PET combined with (18)F-FDG is helpful in characterising the distinct phenotypic features of oestrogen-related tumours; that is, inter- and intrapatient tumour heterogeneity, which indicates its great potential as a determinant of individualised treatment and a prognostic predictor for patients with oestrogen-related tumours.